Masculinité et altertemporalité dans J’apprends l’allemand de Denis Lachaud - David Caron (Itinéraires)
In J’apprends l’allemand, Denis Lachaud offers a homosexual model for the Franco-German “couple”. Given the Nazi heritage, equally impossible to assimilate as to reject, the novel redefines Europe according to a queer and anti-identitarian temporality that disrupts the reassuring masculinist linearity of modernity, making past and present coincide in a truly relational, communitarian dynamic.